Language Role in Forming the Emotional Landscape of “Happier” by Olivia Rodrigo - Salsabila, Irma Nuraeni; Fitriyanti, Elvira (Interdisciplinary Social Studies, 2023)
Background: Songwriters use language in creative ways to create meaning and depth in a song because they want to convey a certain message or emotion. Songwriters use language to paint vivid images and evoke strong emotions in listeners. Aim: This research aims to provide a deeper understanding of how language can influence listeners' emotions and feelings through Olivia Rodrigo's musical artwork entitled Happier. Method: This study uses a qualitative research method with a language and literature analysis approach. The data collection technique is done by literature study. Findings: The results show that language is used to convey various emotions, including heartbreak, regret, and longing. The song lyrics are carefully crafted to create a specific emotional landscape that reflects the narrator's state of mind. In addition, the language used in the song reflects the cultural and social context in which it was created. The lyrics address issues such as social media comparisons, breakups, and the pressure to always be happy. Through the use of language, the song provides commentary on these issues and how they can affect one's emotional landscape.